Epicoccin A Ameliorates PD-like Symptoms in Zebrafish: Enhancement of PINK1/Parkin-Dependent Mitophagy and Inhibition of Excessive Oxidative Stress - Haicheng Ye; Dan Li; Lei Zhang; Yufei Wang; Cong Wang; Meng Jin; Houwen Lin; Peihai Li; Chen Sun; Ning Li (Marine Drugs)
Parkinson’s disease (PD) is the second most prevalent neurodegenerative disorder, yet effective agents for its prevention and therapy remain highly limited. Epicoccin A, a significant secondary metabolite from Exserohilum sp., demonstrates various biological activities; however, its neuroprotective effects have not been elucidated. Here, we investigated the therapeutic potential of epicoccin A for PD by evaluating its impact on neural phenotype, reactive oxygen species (ROS) generation, and locomotor activity in PD-like zebrafish. Transcriptomic analysis and molecular docking were conducted, with key gene expressions further verified using real-time qPCR. As a result, epicoccin A notably mitigated dopaminergic neuron loss, neural vasculature deficiency, nervous system injury, ROS accumulation, locomotor impairments, and abnormal expressions of hallmark genes associated with PD and oxidative stress. Underlying mechanism investigation indicated epicoccin A may alleviate PD-like symptoms by activating PINK1/Parkin-dependent mitophagy, as evidenced by the reversal of aberrant gene expressions related to the pink1/parkin pathway and its upstream mTOR/FoxO pathway following epicoccin A co-treatments. This finding was further confirmed by the robust interactions between epicoccin A and these mitophagy regulators. Our results suggest that epicoccin A relieves PD symptoms by activating pink1/parkin-dependent mitophagy and inhibiting excessive oxidative stress, highlighting its potential as a therapeutic approach for PD.